Research and prospect of 5G edge computing sharing - Lingbin MENG; Juan LI; Nan XUE; Yong ZOU (Dianxin kexue)
The three application scenarios of 5G make forward higher requirements for network delay,bandwidth,connection and security,which drive 5G to sink the core capabilities of network,computing,storage and application to the edge of the network.The 5G base station which is closer to the terminal/user and has complete resources such as base station power,operation and maintenance will be the best choice for 5G edge computing deployment.Based on the multi-point 5G base station site resource and the architecture of edge computing deployment,the feasibility of multi-operator 5G edge computing shared deployment was studied,three feasible co-building and sharing schemes,such as base station infrastructure sharing,IaaS facility sharing and PaaS platform sharing were proposed.By coordinating the development needs of 5G edge computing and realizing the co-construction and sharing of edge computing,the construction cost and operation cost of edge computing can be greatly reduced,and the rapid scale development of edge computing can be realized,to build an intensive and efficient,economic and applicable,intelligent green,safe and reliable edge computing system.